Present and Future Paradigms of Cyberculture in the 21st Century - Atay, Simber (IGI Global, 2020)
Cyberculture is a particularly complex issue. It is seen as a fantastic meeting point of classic philosophers with postmodern theorists, politicians with community engineers, contemporary sophists with software engineers, and artists with rhetoricians. Today, cyberculture is identified highly with new media and digital rhetoric and could be used to create a comprehensive map of modern culture. Present and Future Paradigms of Cyberculture in the 21st Century is a comprehensive research publication that explores the influence of the internet and internet culture on society as a whole. Highlighti.